2014
DOI: 10.1111/jipb.12189
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for discriminating Zingiberaceae species in India using DNA barcodes

Abstract: We evaluated nine plastid (matK, rbcL, rpoC1, rpoB, rpl36-rps8, ndhJ, trnL-F, trnH-psbA, accD) and two nuclear (ITS and ITS2) barcode loci in family Zingiberaceae by analyzing 60 accessions of 20 species belonging to seven genera from India. Bidirectional sequences were recovered for every plastid locus by direct sequencing of polymerase chain reaction (PCR) amplicons in all the accessions tested. However, only 35 (58%) and 40 accessions (66%) yielded ITS and ITS2 sequences, respectively, by direct sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 74 publications
4
40
1
Order By: Relevance
“…As a consequence, we generated 60 species signatures to classify closely related sequences by using the PSSM information (Additional file 5). These results are consistent with earlier plant DNA barcoding studies that mentioned matK as a suitable barcode; this gene can discriminate morphologically similar and closely related species [13, 20, 30, 31]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a consequence, we generated 60 species signatures to classify closely related sequences by using the PSSM information (Additional file 5). These results are consistent with earlier plant DNA barcoding studies that mentioned matK as a suitable barcode; this gene can discriminate morphologically similar and closely related species [13, 20, 30, 31]. …”
Section: Discussionsupporting
confidence: 92%
“…Seven chloroplast loci have been tested for plant species identification by The Consortium for the Barcode of Life (CBOL) Plant Working Group, where the suitability of matK and rbcL loci as a barcode was showed [12]. Vinitha et al [13] studied a total of 20 species belonging to the family Zingiberaceae from India by using nine plastids and two nuclear loci and reported that matK and rbcL aids in the determination of 15 species (75%) into monophyletic groups. Techen et al [14] mentioned that the matK region was preferred as a barcode candidate because of high evolutionary rate, low transition/transversion rate, and inter-specific divergence.…”
Section: Introductionmentioning
confidence: 99%
“…9,12) Using clone sequencing for ITS-LSU D1/D3, we identified 2-10 haplotypes within each sample. Our results are consistent with other studies 10,11) reported different ITS sequences among specimens. Therefore, our findings support the use of clone sequencing rather than the direct sequencing of PCR products to obtain accurate sequence data for ribosomal DNA (rDNA) fragments (ITS, ITS2, ITS-LSU D1/D3).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies tested the ability of DNA barcoding to identify Curcuma species. [9][10][11][12] This research yielded sequence data that are stored in GenBank and can be used as a reference library. To improve the efficiency of rbcL and matK, we used the nuclear ribosome fragment ITS-LSU D1/D3 (Fig.…”
mentioning
confidence: 99%
“…However, DNA barcoding has been emerging as the primary diagnostic strategy for authentication of plant material used for the preparation of HMPs. In this regard, a large number of nuclear and plastid DNA based barcodes have now become a realistic and accurate diagnostic tool for identification of genuine plant species and determination of adulterants in herbal products (Mahadani and Ghosh, 2013, Pang et al , 2013, Selvaraj et al , 2012, Thompson and Newmaster, 2014, Vinitha et al , 2014. A novel DNA mini-barcode assay, as developed for the authentication of G. biloba herbal supplements with a high degree of sensitivity and specificity (Little, 2014), has offered a practical resolution to authenticate herbal supplements both for manufacturers and regulatory authorities.…”
Section: Dna Barcoding and Metabolite Profiling Can Resolve The Qualimentioning
confidence: 99%